A New Perspective for Understanding School Managers' Roles: The Impact of Principals' Boundary Activities on the Effectiveness of School Management Teams. Issue 3 (March 2018) - Benoliel, Pascale; Somech, Anit
Background/Context: Increasingly, educational leadership research has stressed that leadership is not solely embedded in formal roles but often emerges from relationships between individuals. Senior management teams (SMTs) are an important expression of a formal management structure based on the principle of distributed leadership. Such structures may require a reconceptualization of school leadership and the role of the principal in such a way as to better meet new challenges and enable principals to manage SMTs more effectively. Accordingly, it is proposed that to improve effectiveness, principals engage in boundary activities, the principals' internal activities directed toward the SMT aimed at dealing with internal team matters and the principals' external activities directed toward external agents in the team's focal environment to acquire resources and protect the team. Purpose/Objective: The present study attempts to advance a theoretical model of principals' internal and external activities toward their SMTs. This study's purpose is twofold: First, the study tries to determine which of the internal and external activities principals engage in more frequently and less frequently and to what extent. Second, the study attempts to determine how these activities are related to the SMT effectiveness outcomes: in-role performance and innovation. Taking on a distributive perspective to school leadership, our goal is to extend our knowledge about the activities that might facilitate SMT effectiveness, by highlighting the principal boundary activities as fundamental. Research Design: Quantitative study. Data Collection and Analysis: Data were collected from two sources to minimize problems associated with same source bias: 92 SMTs and their principals from 92 public schools in Israel. Principals evaluated the SMTs' effectiveness through validated surveys of team in-role performance and team innovation, and SMT members evaluated the internal and external activities of the principal. Findings/Results: ANOVA analyses indicate significant mean differences between the principal's internal and external activities. Results from Structural Equation Model indicate that internal activities were related to SMT performance, whereas external activities were related to SMT innovation. Conclusions/Recommendations: Principals who manage both the internal SMT dynamic by promoting SMT identity and building team trust, while also promoting a common mission, serve the role of coordinator between SMT members and constituencies external to the SMT, enhancing SMT effectiveness. It may be, then, that studying new models of school leadership and management, including the relationship of the principal and the SMT, may deepen our understanding of the increasingly complex role of principals today.